Opmitalisasi Kesadaran Sosial Berkarakter Generasi Muda Islam melalui Organisasi Santri Intra Madrasah (OSIM) - Rozi, Fathor; Alviantika, Alviantika; Ula, Najmil Faizatul; Laila, Nor; Widiawati, Ayu; Diyah, Shofwatun Naqsyaban (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
The purpose of this study was to determine OSIM activities, the time and process of implementing OSIM activities, and social awareness of student character with OSIM activities. This study uses a qualitative approach with a case study as the type of research. The location of this study is at Madrasah Diniyah Darul Lughah Wal Karomah, Sidomukti Village, Probolinggo District. The data collection techniques used were observation and interviews. While the data analysis techniques used were data reduction, data presentation, and drawing conclusions. The results of the study showed that there were several activities initiated by OSIM including the Election of the Chairman and Deputy Chairman of OSIM, LPJ evaluation, comparative studies, and class meetings. The implementation of several activities is the Election of the Chairman and Vice Chairman of OSIM is usually held a week before the previous OSIM term ends, the evaluation of the LPJ (Accountability Report) is carried out every month and the annual report is transparently in front of the female teachers and all students which is held 1 week after the election of the new OSIM chairman, comparative studies are carried out at the beginning of the new OSIM management period every year, and class meetings are held after the final exams of the madrasah. There are several forms of social awareness with the OSIM activities, namely Leadership Training, Organizational Skills, Communication Skills, Decision Making Skills, More Confident, Experience Working on Projects, Learning to Build Networks, and Positive Contributions to Schools.